Entre mimese e diegese : a construção da cena na adaptação de Closer - Silva, Marcel Vieira Barreto (2008)
The idea of this work is to analyze the cinematographic adaptation of the play Closer (1997), by Patrick Marber, directed by Mike Nichols in 2004. In the dramatic text, one of the main themes is the question of the gaze, which means, how the characters are constantly involved in schemes of possibility/impossibility of seeing, or desire to see/be seen. In this sense, the play creates situations in which the modes of engagement between the public and the staging are ruled by a dialectics between the dialogues established by those schemes and the immobility of the fixed gaze in the scenic architecture of the Italian stage. On the other hand, the film Closer transforms the question of the gaze in the central structure of the narrative composition, which means, it does not only make the gaze its theme, but also its form. Because the schemes of possibility/impossibility of seeing are organized by the mobility of the points of view (from the narrative authority, the characters and the audience), and the desire to see/be seen becomes determinant of the dynamics of the miseen- scène, the editing and the materiality of the gaze by the camera. With this in mind, we will try to analyze in a comparative way, the cinematographic adaptation of Closer, putting in evidence the construction of the scene in these two works: in the dramatic text, the scene is a visually fixed construct, mediated by the dialogues of the characters and by the text indications of the movement of actors on stage; in the film, the scene is actually a set of gazes on the scene, and defines itself only from the orchestration of points of view created by the filmic narrative.